Urban History and the Politics of the Property Tax: The Case of Single Residential Property in the City of Toronto, 1920s-1970s - White, Randall (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1986)
In the more recent past, property tax reform in the City of Toronto has been thwarted by suggestions of "progressive elements" in the single residential tax base, that hold out prospects of regressive shifts in the residential tax burden in the wake of a reassessment. Study of the evolution of the tax base in five city neighbourhoods since the early 1920s indicates that these progressive elements are largely an unintended consequence of historical changes in neighbourhood real estate markets. Moreover, what potential there is for regressive tax shifts could be offset significantly by some updated form of a partial graded dwelling house exemption in the City's traditional property tax system. The urban history of the Toronto property tax, however, does illustrate the political and technical challenges of property tax reform through market value assessment.